Tinjauan Hukum Islam Terhadap Peran Ganda Istri sebagai Pencari Nafkah Utama dalam Keluarga (Studi Kasus di Desa Kasang Pudak Kecamatan Kumpeh Ulu Kabupaten Muaro Jambi) - Alda Fita Loka; Ramlah Ramlah; Idris Idris; Jalaluddin FA (Fakultas Syariah Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, Indonesia, 2022)
This paper examines the dual roles of the wife as the main breadwinner in the family in terms of Islamic law that occurred in Kasang Pudak Village. The paper aims to find out the background factors and look at the Islamic law of the wife making the main breadwinner in the family in the Kasang Pudak Village community. This paper research method is normative sociological qualitative, which refers to the social rules that apply in society using a qualitative approach to the method of collecting data through interviews and documentation. Based on the results of the research that has been done, the researcher draws conclusions, first, there are several factors behind the occurrence of the dual role of the wife in the family in Kasang Pudak Village, Kumpeh Ulu District, Muaro Jambi Regency, namely economic factors, the husband's lack of skills, and educational factors, lazy work factors, as well as the factor of lack of understanding of religion, especially the law in family. Second, in the review of Islamic law regarding the breadwinner's wife, there are several scholars who differ in opinion, some of whom have the opinion of mubah (permissible) and some who do not. First, this group of scholars is of the opinion that it is permissible, because in Islam it does not prohibit women from working outside the home, as long as they understand the conditions that are permissible for women to work and they can fulfill them. Second, according to scholars who argue like this, basically the law on a wife working outside the home is prohibited, because by working outside the home there will be many obligations she must leave.